Eksistensi Ratam Bagi Penanaman Visi Dan Misi Prodi Teologi Hindu Di STAHN Mpu Kuturan Singaraja - I Wayan Kariarta; Komang Heriyanti; Ni Made Evi Kurnia Dewi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Ratam activities in the Hindu Theology Study Program are held in the framework of campus life orientation for new students (maba). In the implementation of ratam activities there are efforts to build communication and familiarity between all academic communities in the Hindu Theology Study Program. The vision of the Hindu Theology Study Program is: "Superior and Dignified Study Program of Tri Kaya Parisudha character". While the mission of the Hindu Theology Study Program is 1) Organizing quality Hindu Theology education to produce graduates of character, superiority and dignity; 2) Conduct innovative research in the development and application of Hindu Theology. 3) Organize community service in the field of Hindu Theology. Understanding of the vision and mission of the Hindu Theology Study Program by all academic community contained in it, is the fundamental point that determines the success of the work program that has been established. The background of the ratam is to socialize the vision of the Hindu Theology Study Program mission and strengthen the sense of brotherhood for the academic community in the Hindu Theology Study Program. Through the socialization of vision and mission, it is hoped that it can strengthen the understanding of the values contained in the concept of Tri Kaya Parisudha and increase solidarity between academic community in Hindu Theology Study Program.